STUDY OF THE POTENTIAL OF ETHNOSCIENCE AND LOCAL WISDOM AS A MEDICINAL PLANT IN SMK PEMBANGUNAN - RADHIA TIL HANNOUM (SEMESTA: Journal of Science Education and Teaching, 2022)
So far, there have been many types of plants used by the people of Lubuk Minturun and Limau Lunggo. The problem is that until now there are not many plants that are clearly identified both about the names of these plant species scientifically and their benefits. The purpose of this study was to determine the types of plants that are useful as medicinal plants in the people of Lubuk Minturun and Limau Lungo and their properties. This research was carried out in September 2019 at SMK Pertanian Pembangunan Negeri Padang and Limau Lungo KecematanLembang Jaya, Solok Regency. This study used descriptive methods and interviews. The results showed that there are 15 plants that are efficacious as traditional medicinal plants.